Performance Appraisal System using Multifactorial Evaluation Model - Chen, Yoke Yie; Yee, Chia Chai (2009)
Performance appraisal of employee is important in managing the human resource of an organization. With the change towards knowledge-based capitalism, maintaining talented knowledge workers is critical. However, management classification of “outstanding”, “poor” and “average” performance may not be an easy decision. Besides that, superior might also tend to judge the work performance of their subordinates informally and arbitrarily especially without the existence of a system of appraisal. In this paper, we propose a performance appraisal system using multifactorial evaluation model in dealing with appraisal grades which are often express vaguely in linguistic terms. The proposed model is for evaluating staff performance based on specific performance appraisal criteria. The project was collaboration with one of the Information and Communication Technology company in Malaysia with reference to its performance appraisal process.